Ok...so u have 4 people sharing this plan...they each pay for their own data..however, the $ 90 flat rate is split between them equally.
90/4 = 22.5....so each of them pay 22.50 each for the flat rate.
so John's equation is : 22.5 + 0.25x = 147.50
Answer:
2x + 5y + 28 = 0
Step-by-step explanation:
since they are perpendicular,
m1 ×m2 = -1
5/2 × m2 = -1
m2 = -2/5
now,
y -y1 = M (x-x1)
y - (-4) = -2/5 ( x - (-4) )
y +4 = -2/5 ( x + 4 )
5 ( y +4 ) = -2 ( x+4)
5y +20 = -2x - 8
2x + 5y +20 + 8 =0
2x + 5y + 28 = 0
In a square all 4 sides are equal, so when you cut it along the diagonal to make a triangle, both the base and the height of the triangle would be the same.
The area of a triangle is found by the formula 1/2 x base x height
Since the base and height are the same the formula becomes Area = 1/2 x S^2 ( where S is the length of a side).
The area is given as 0.72 square units.
Now you have 0.72 = 1/2 x S^2
First multiply both sides by 2:
1.44 = S^2
To find S, take the square root of both sides:
S = √1.44
S = 1.2
The side length is 1.2 units.
Answer:
The value of
. The figure is also attached below.
Step-by-step explanation:
Considering the expression
![5x + 6(x - 2) - 8 (x - 3)](https://tex.z-dn.net/?f=5x%20%2B%206%28x%20-%202%29%20-%208%20%28x%20-%203%29)
If we have to find the vale of
, then
![5x + 6(x - 2) - 8 (x - 3)=0](https://tex.z-dn.net/?f=5x%20%2B%206%28x%20-%202%29%20-%208%20%28x%20-%203%29%3D0)
![5x+6x-12-8\left(x-3\right)=0](https://tex.z-dn.net/?f=5x%2B6x-12-8%5Cleft%28x-3%5Cright%29%3D0)
![5x+6x-12-8x+24=0](https://tex.z-dn.net/?f=5x%2B6x-12-8x%2B24%3D0)
![3x+12=0](https://tex.z-dn.net/?f=3x%2B12%3D0)
![\mathrm{Subtract\:}12\mathrm{\:from\:both\:sides}](https://tex.z-dn.net/?f=%5Cmathrm%7BSubtract%5C%3A%7D12%5Cmathrm%7B%5C%3Afrom%5C%3Aboth%5C%3Asides%7D)
![3x+12-12=0-12](https://tex.z-dn.net/?f=3x%2B12-12%3D0-12)
![3x=-12](https://tex.z-dn.net/?f=3x%3D-12)
![\mathrm{Divide\:both\:sides\:by\:}3](https://tex.z-dn.net/?f=%5Cmathrm%7BDivide%5C%3Aboth%5C%3Asides%5C%3Aby%5C%3A%7D3)
![\frac{3x}{3}=\frac{-12}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B3x%7D%7B3%7D%3D%5Cfrac%7B-12%7D%7B3%7D)
![x=-4](https://tex.z-dn.net/?f=x%3D-4)
Therefore, the value of
. The figure is also attached below.
Keywords: equation
Learn more about equation solution from brainly.com/question/13678520
#learnwithBrainly
Answer:
x = 11
Step-by-step explanation:
Given :
AB = x + 5
BC = 2(x - 3)
AB = BC
AB = BC
x + 5 = 2(x - 3)
x + 5 = 2x - 6
5 + 6 = 2x - x
11 = x
x = 11
happy to help :)